Inclusion of Pediatric Samples in an Opt‐Out Biorepository Linking DNA to De‐Identified Medical Records: Pediatric BioVU. Issue 2 (21st November 2012) - McGregor, T L; Van Driest, S L; Brothers, K B; Bowton, E A; Muglia, L J; Roden, D M
<x xml:space="preserve">Abstract</x> The Vanderbilt DNA repository, BioVU, links DNA from leftover clinical blood samples to de‐identified electronic medical records (EMRs). After initiating adult sample collection, pediatric extension required consideration of ethical concerns specific to pediatrics and implementation of specialized DNA extraction methods. In the first year of pediatric sample collection, more than 11, 000 samples from individuals younger than 18 years were included. We compared data from the pediatric BioVU cohort with those from the overall Vanderbilt University Medical Center pediatric population and found similar demographic characteristics; however, the BioVU cohort had higher rates of select diseases, medication exposures, and laboratory testing, demonstrating enriched representation of severe or chronic disease. The fact that the sample accumulation is not balanced may accelerate research in some cohorts while limiting the study of relatively benign conditions and the accrual of unaffected and unbiased control samples. BioVU represents a feasible model for pediatric DNA biobanking but involves both ethical and practical considerations specific to the pediatric population. Clinical Pharmacology & Therapeutics (2013); 93 2, 204–211. doi:10.1038/clpt.2012.230